L-shaped association between fasting blood glucose and urea in a non-diabetic population - Wu, Chenguang; Xu, Zhenyan; Chen, Xin; Liu, Hualong; Chen, Yuliang; Huang, Jiaxing; Lu, Teng; Huang, Zixi (Frontiers in Nutrition, 2025)
BackgroundThe relationship between fasting blood glucose and urea in non-diabetic individuals is still unclear. This study aimed to evaluate the association between fasting blood glucose and urea in a non-diabetic population.MethodsData from a cohort of non-diabetic individuals were collected from the 2009 China Health and Nutrition Survey dataset. We performed smooth curve and two piecewise linear regression analyses to assess the association between fasting blood glucose and urea in this non-diabetic population.ResultsData from a total of 7,596 adult participants without diabetes were included in this study; the mean age of the participants was 50.2 years, and 46.4% were male. There was an L-shaped relationship between fasting blood glucose and urea, and the inflection point of fasting blood glucose was 4.6 mmol/L. After adjusting for potential confounders, we found a negative correlation between fasting blood glucose and urea up to the inflection point (β = −0.3, 95% CI −0.5 to −0.2, P < 0.001), but beyond the inflection point, this relationship disappeared (β = 0.0, 95% CI −0.1 to 0.1 P = 0.848). In the group with lower fasting blood glucose (fasting blood glucose <4.6 mmol/L), smoking (interaction P = 0.037) and alcohol consumption (interaction P = 0.001) influenced the relationship between fasting blood glucose and urea.ConclusionsThe results suggest that lower fasting blood glucose was associated with higher urea in non-diabetic individuals with fasting blood glucose <4.6 mmol/L, revealing an L-shaped association between fasting blood glucose and urea.